The Social Development and Revitalisation Process of the Heritage Town of Muntok in West Bangka - Kemas Ridwan Kurniawan (International Journal of Built Environment and Scientific Research, 2017)
This paper discusses the overall importance of society in the revitalisation process of the Heritage Town of Muntok. It was triggered by the phenomena of the society’s declining confidence. Theoretically, the members of society became the main actors for the urban development. In Muntok, the members of society became sceptical about any revitalisation initiatives or social development proposals due to the unpredictable economic future. As a pilot project for this social development, the revitalisation of one of the Malay Stage Houses in Kampung Tanjung Muntok is expected to change people’s mindset about the importance of heritage in order to build up society’s confidence. This paper is based on my research experience and community engagement in the town of Muntok from 2012 until present.  This paper will look at how the strategies to build up society’s confidence evolved during heritage revitalisation process. Our findings indicate that capacity transformation and capacity building were important outcomes achieved during the process.